Cardiospecific troponins in non-ischemic cardiological pathologies - Giuseppe Lippi; Martina Montagnana; Gian Cesare Guidi (Emergency Care Journal, 2006)
Cardiospecific troponin T (TnT) and I (TnI) are low-molecularweight proteins that form part of the troponin complex and are integral components of the myofibrillar contractile apparatus of the heart. Loss of integrity of cardiac myocyte membranes causes release of cardiac troponins into the circulation, which can be detected by highly sensitive assays for cTnT and cTnI developed to the stat diagnosis of acute coronary syndrome. Regardless of preanalytical and analytical sources (incorrect collection or handling of the specimen, malfunctioning of the analyzer, heterophilic antibodies), a diagnostic troponin value is expression of myocardial damage, though it does not provide definitive clue on the nature of such an increment. In fact, increases in serum cardiac troponins also occur in the absence of cardiac ischemia and may sometimes led to an inappropriate or unjustified clinical decision making. Abnormal troponin values in plasma are frequently observed in various clinical contexts independent from the acute coronary disease, like myocarditis, pulmonary embolism, acute heart failure, septic shock, and as a result of cardiotoxic drugs as well as after therapeutic procedures like coronary angioplasty, electrophysiological ablations, or electrical cardioversion. Awareness of this issue is essential to either prevent unjustified alarmism or underestimation of clinical situations that may finally compromise the patient’s health.